Alguns aspectos que influenciam a escolha e o uso do livro didático pelos professores das ciências naturais na educação básica. - Luciana Campos Miranda (2009)
x This dissertation presents a study of the selection and use of basic level natural sciences educational books, the focus of which being mainly on investigating (i) the criteria adopted by basic level natural sciences teachers in the process of selecting a given educational book and (ii) some aspects of how the book is used by these teachers. The first phase of this investigation comprised a structured questionnaire filled out by 226 science teachers, which provided quantitative data on some peculiarities of the selection process at schools, as well as the criteria adopted by teachers for the selection of such books and how the books are used by the teachers. Further on, the second phase comprised semi-structured thought-provoking interviews, which were conducted individually with eight science teachers and from which qualitative data were collected on the aspects addressed in the questionnaire. The assessment of the data took into account the prevailing conditions at the school under which the selection of the book and how it will be used occurs, as well as some of the teachers' premises and beliefs about these processes. In what concerns the criteria adopted for the selection of educational books, it was noticed that the teachers focus mainly on the accessible language used across the texts and exercises. Other aspects highly valued by the teachers have to do with the contextualized and interdisciplinary approaches, practice- and investigation-driven activities and illustrations. Among the most common ways of using educational books, the use of exercises and text reading stand out. The criteria adopted by teachers for the selection of educational books are related to how they will use the book, their beliefs on what make up good science teaching methods and to their awareness of the students profile. According to the teachers, any non-compliance with some teaching practices deemed important was attributed either to the peculiar restrictions of the school's reality or to the lack of the required methodological knowledge for the enforcement of such practices. Based on the analysis of these data, we drew to the conclusion that as far educational books are concerned the selection method adopted by the teachers is influenced by the conflicts between knowledge and beliefs arising out of a number of sources, and also by the school's reality within which the teachers themselves are inserted. Our final considerations will address the implications of this work suggesting that a research on the sciences educational area be conducted focused mainly on the qualification of teachers.